If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + -1b + -4c = p Solving a + -1b + -4c = p Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'b' to each side of the equation. a + -1b + b + -4c = b + p Combine like terms: -1b + b = 0 a + 0 + -4c = b + p a + -4c = b + p Add '4c' to each side of the equation. a + -4c + 4c = b + 4c + p Combine like terms: -4c + 4c = 0 a + 0 = b + 4c + p a = b + 4c + p Simplifying a = b + 4c + p
| 5x+22=3+8x-8 | | 36x^2+69x+36=0 | | -5x+4y-5z=-6 | | 25b^2=64 | | 0.01(x+4)-0.04=0.001(5x+4) | | 173+10x=-100+17x | | 4s-3-2s-6=9 | | y+10-8y=-2y-y+18 | | 7x+20=8x+8 | | 6.7+1.9n=1.19 | | x^2+128x+375=750 | | 6+8x=-98 | | -5x-18=108 | | 9+8k=31 | | 9+8k=31 | | -3+4x=5 | | r-s-2=p | | 2(9x-3)=22x-50 | | -4x+6y-9z=2 | | 2.5y+3.6y=90 | | 4x+7=-89 | | 4+6=4 | | 5(x-7.2)=15.5 | | -3(3x-11)+2(5x+7)= | | 6+(2+1)=5-5t | | 8y+1=2y+25 | | 4x-15=3x+9 | | 0.8n+9=0.2(4n+45) | | 2x+5+6x=3x+15 | | 7y-1=35-5y | | 0.4(2x+6)+0.1=0.5(2Z-3) | | 2(x+y)+6n(x+y)= |